An ultra-light high-toughness heat-resistant aluminum-magnesium alloy ingot and plate and a preparation method thereof

CN122879565APending Publication Date: 2026-10-09TAIYUAN UNIVERSITY OF TECHNOLOGY
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202611279570.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-21
Publication Date
2026-10-09

AI Technical Summary

Technical Problem

最终以低成本制备出密度低于铝锂合金(≤2.67 g/cm³)的超轻高强韧耐热铝镁合金铸锭及轧制板材,兼顾高强度、高塑性与优异热稳定性的协同匹配,满足轻量化结构件对高性能铝合金材料的应用需求,解决了高镁Al-Mg合金强塑性失配与高温热稳定性不足的难题

Benefits of technology

[0009]与现有技术相比,本发明提供的超轻高强韧耐热铝镁合金铸锭具有以下有益效果,首先,本发明的()复合球磨颗粒经高能球磨后,Al基体壳层在熔炼时优先熔化,将和TiC颗粒均匀释放至铝基体中,形成“预分散—缓释—均匀分布”机制,使和TiC颗粒在基体中均匀弥散分布,既能够以高温稳定陶瓷相为异质形核核心细化α-Al晶粒,又可通过Orowan效应与热错配效应同步提升基体强度,同时颗粒在高温下可钉扎晶界与位错,为合金提供基础的耐热稳定性。其次,本发明通过Sc元素、Zr元素与()复合球磨颗粒的协同添加,从凝固源头实现了对粗大β相的有效抑制。具体而言,Sc与Zr形成的纳米共格粒子,与、TiC颗粒构成双重异质形核体系,显著细化α-Al晶粒并减小二次枝晶间距,既缩短了Mg原子的扩散距离、大幅减轻枝晶偏析,从根源上降低晶界非平衡共晶粗大β相的生成倾向,又通过增加晶界总面积促使残余β相以细小断续的颗粒状弥散分布,避免连续网状有害组织的形成。此外,Sc、Zr原子在晶界的偏聚可降低晶界能并提高β相非均匀形核能垒,纳米相对晶界的Zener钉扎作用进一步限制β相沿晶界的连续生长与粗化;、TiC颗粒亦可作为β相的异质形核位点,促进其在基体内部弥散析出,结合共格粒子自身的析出强化作用,共同优化铝镁合金铸锭的强塑性匹配。在耐热性能方面,粒子与陶瓷颗粒均具备优异的高温结构稳定性,可协同阻碍高温下的晶界迁移与再结晶进程,有效抑制合金的高温强度衰减。在特定添加量的Mg与复合球磨颗粒、Sc元素、Zr元素的协同作用下,本发明的铝镁合金铸锭具有高强度、高塑性和优异的热稳定性,铸锭的抗拉强度≥369MPa,屈服强度≥280MPa,伸长率≥4.6%,同时合金密度≤2.54g/cm³,能够满足轻量化需求。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122879565A_ABST
    Figure CN122879565A_ABST
Patent Text Reader

Abstract

The application discloses an ultra-light high-strength heat-resistant aluminum-magnesium alloy ingot and plate and a preparation method, and relates to the technical field of non-ferrous metal preparation. The ultra-light high-strength heat-resistant aluminum-magnesium alloy ingot contains the following components in percentage by mass: Mg: 7-11%, Sc: 0.1-0.4%, Zr: 0.1-0.3%, () composite ball-milled particles: 1.5-2.5%, and the balance of Al and inevitable impurities; wherein the () composite ball-milled particles contain Al powder, powder and TiC powder; the ultra-light high-strength heat-resistant aluminum-magnesium alloy ingot and plate have the characteristics of low density, high strength, high plasticity and toughness and high thermal stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of non-ferrous metal preparation technology, specifically relating to an ultra-lightweight, high-strength, tough, and heat-resistant aluminum-magnesium alloy ingot and plate, and their preparation method. Background Technology

[0002] Aluminum-magnesium (Al-Mg) alloys are widely used in lightweight applications such as aerospace, marine engineering, and rail transportation due to their low density, good corrosion resistance, and weldability. Magnesium exhibits a significant solid solution strengthening effect in the aluminum matrix, with a limiting solid solubility of up to 17.4 wt.% at the eutectic temperature. Each 1 wt.% increase in Mg can increase the alloy strength by approximately 35 MPa and decrease the density by approximately 0.5%. However, the solid solubility of magnesium at room temperature is extremely limited (<1.9 wt.%). When the Mg content exceeds 3.5 wt.%, supersaturated Mg, under prolonged exposure at room temperature or at medium temperatures (50–200 °C), continuously precipitates coarse, incoherent precipitates along the grain boundaries. This phase induces intergranular embrittlement and leads to increased stress corrosion susceptibility (i.e., sensitization), while simultaneously accelerating grain coarsening and high-temperature strength decay, severely restricting the hot workability and service reliability of the alloy. Due to this limitation, the Mg content in traditional 5XXX series aluminum alloys is typically controlled below 5.5 wt.%, which is insufficient to meet the urgent performance requirements of next-generation ultralight, high-strength, high-toughness, heat-resistant, and corrosion-resistant high-end aluminum alloy components in high-speed flight fields such as aerospace and transportation.

[0003] To address the bottlenecks of limited magnesium content in aluminum-magnesium alloys, insufficient strength and toughness in high-magnesium aluminum alloys, and poor corrosion and heat resistance, Xiong Baiqing's team conducted systematic research. Chinese patent CN116065066A discloses an Al-Mg-Zn-Si system of lightweight, high-strength, and corrosion-resistant aluminum alloy, which, after semi-continuous casting, multi-stage homogenization, deformation, and solution aging treatments, induces… and Biphasic precipitation synergistically enhances and inhibits The alloy exhibits a low density of 2.64 g / cm³, a tensile strength ≥420 MPa, and a spalling corrosion rating not lower than EA. Building upon this, Chinese patent CN121718770A further optimizes the aluminum alloy to a high Zn, low Si composition, promoting [further improvement] through precise control of the Mg / Zn / Si ratio. The phase precipitates densely and induces grain boundaries. Phase transformation fills the grain boundary precipitate-free zone; after homogenization, deformation, and solution aging treatment, the alloy density is as low as 2.68 g / cm³, and the tensile strength is ≥490MPa, achieving a higher level of strength and toughness matching. However, this system has a significant drawback: high Si easily forms coarse aggregates. The addition of high-density Zn elements weakens the advantages of lightweighting and damages plasticity. The preparation relies on complex processes such as extrusion or forging deformation, and the high-temperature thermal stability is insufficient, making it difficult to meet the performance maintenance requirements in medium-temperature service scenarios of 50~200℃.

[0004] Min et al. mixed Al-8Mg-0.6Sc-0.4Zr-0.6Si-0.6Mn powder with 1 wt.% TiB2 powder and prepared a TiB2 / Al-Mg-Sc alloy by selective laser melting. The alloy had a yield strength of 412 MPa, a tensile strength of 483 MPa, and an elongation of 15.8% (Effects of TiB2 additions on microstructure and mechanical properties of Al-Mg-Sc alloy fabricated by selective laser melting, Journal of Materials Research and Technology, 2023, 23: 3537-3546). However, this alloy has drawbacks such as large fluctuations in the tensile curve, high Sc content, limited sample size, and high preparation cost.

[0005] Besides toughening and forming processes, the thermal stability of high-Mg content Al-Mg alloys is also a key issue restricting their application, but there are few related research reports. Cha Min et al. (Mechanism of high strength, plasticity and high thermal stability of high-solid-solution Al-Mg alloys under controlled rolling with high-strain liners at low temperature. Acta Metallurgica Sinica, 2024, 60 (4): 473-484) obtained room temperature yield strength (YS) of 527 MPa, tensile strength (UTS) of 597 MPa and elongation of 7.7% by controlled rolling of high-strain liners under extrusion-liquid nitrogen. Although the high strength and good plasticity of Al-9Mg alloy were achieved, after annealing at 300℃ for 30 min, the strength dropped to YS=300 MPa and UTS=470 MPa; after annealing at 400℃ for 30 min, the strength dropped sharply to YS=170 MPa and UTS=385 MPa, indicating poor thermal stability of microstructure and properties.

[0006] In summary, high-magnesium aluminum alloys still face bottlenecks in their manufacturing process, such as a mismatch between lightweight, strong, tough, and heat-resistant properties, complex processes, expensive equipment, and limited specifications. These bottlenecks severely restrict their engineering applications in the aerospace and transportation fields. Summary of the Invention

[0007] To address the aforementioned technical problems, this invention provides an ultralight, high-strength, high-toughness, and heat-resistant aluminum-magnesium alloy ingot and sheet, as well as a preparation method. The core technical approach of this invention is "breaking through the Mg solid solubility limit, Sc / Zr nanophase regulation, and multi-scale heterogeneous microstructure design." By optimizing the alloy composition design, effective control of nano-precipitates and equiaxed grains is achieved under ordinary gravity casting conditions. Ultimately, ultralight, high-strength, high-toughness, and heat-resistant aluminum-magnesium alloy ingots and rolled sheets with densities lower than aluminum-lithium alloys (≤2.67 g / cm³) are prepared at low cost. This achieves a synergistic match of high strength, high plasticity, and excellent thermal stability, meeting the application requirements of lightweight structural components for high-performance aluminum alloy materials and solving the problems of strength-plasticity mismatch and insufficient high-temperature thermal stability in high-magnesium Al-Mg alloys.

[0008] To achieve the above objectives, a first aspect of the present invention provides an ultralight, high-strength, high-toughness, and heat-resistant aluminum-magnesium alloy ingot, wherein, by mass percentage, the ultralight, high-strength, high-toughness, and heat-resistant aluminum-magnesium alloy ingot comprises the following components: Mg: 7%-11%, Sc: 0.1%-0.4%, Zr: 0.1%-0.3%, ( Composite ball milling particles: 1.5%-2.5%, balance being Al and unavoidable impurities; Among them, the ( The composite ball milling particles contain Al powder, Powder and TiC powder.

[0009] Compared with the prior art, the ultralight, high-strength, tough, and heat-resistant aluminum-magnesium alloy ingot provided by the present invention has the following beneficial effects. First, the present invention ( After high-energy ball milling, the Al matrix shell of the composite ball milled particles preferentially melts during smelting, thus... TiC particles are uniformly released into the aluminum matrix, forming a "pre-dispersion-slow release-uniform distribution" mechanism, which enables... The uniform dispersion of TiC particles in the matrix not only refines α-Al grains using a high-temperature stable ceramic phase as a heterogeneous nucleation core, but also simultaneously enhances matrix strength through the Orowan effect and thermal mismatch effect. Furthermore, the particles can pin grain boundaries and dislocations at high temperatures, providing fundamental thermal stability for the alloy. Secondly, this invention utilizes Sc, Zr, and (… The synergistic addition of composite ball-milled particles effectively suppressed coarse β-phase at the solidification source. Specifically, the nano-coherent structure formed by Sc and Zr... Particles, and TiC particles constitute a dual heterogeneous nucleation system, significantly refining α-Al grains and reducing secondary dendrite spacing. This shortens the diffusion distance of Mg atoms, greatly reduces dendrite segregation, and fundamentally reduces the tendency for the formation of coarse β-phase in non-equilibrium eutectic grain boundaries. Furthermore, by increasing the total grain boundary area, it promotes the dispersed distribution of residual β-phase in fine, discontinuous granular form, avoiding the formation of continuous, harmful network structures. In addition, the segregation of Sc and Zr atoms at grain boundaries lowers the grain boundary energy and increases the energy barrier for heterogeneous nucleation of the β-phase. Zener pinning relative to grain boundaries further restricts the continuous growth and coarsening of the β phase along grain boundaries; TiC particles can also serve as heterogeneous nucleation sites for the β phase, promoting its diffuse precipitation within the matrix and coherent bonding. The precipitation strengthening effect of the particles themselves optimizes the strength-ductility balance of the aluminum-magnesium alloy ingot. Regarding heat resistance, Both Mg and ceramic particles possess excellent high-temperature structural stability, synergistically hindering grain boundary migration and recrystallization processes at high temperatures, effectively suppressing the high-temperature strength decay of the alloy. With specific addition amounts of Mg and... Under the synergistic effect of composite ball milling particles, Sc element, and Zr element, the aluminum-magnesium alloy ingot of the present invention has high strength, high plasticity, and excellent thermal stability. The tensile strength of the ingot is ≥369MPa, the yield strength is ≥280MPa, the elongation is ≥4.6%, and the alloy density is ≤2.54g / cm³, which can meet the requirements of lightweighting.

[0010] Furthermore, the ( In the composite ball milled particles, the Al powder, the... The mass ratio of powder to TiC powder is (1-3):1:1.

[0011] Furthermore, the Al powder, the The average particle size of the powder and the TiC powder are each independently 1 μm-3 μm.

[0012] In this invention, when Al powder, When the mass ratio of powder to TiC powder and the average particle size meet the above range... The uniform dispersion of TiC particles in the matrix further reduces the tendency of the formation of coarse β phase in non-equilibrium eutectic at grain boundaries, resulting in ultra-lightweight, high-strength, tough, and heat-resistant aluminum-magnesium alloy ingots, as well as plates made from ultra-lightweight, high-strength, tough, and heat-resistant aluminum-magnesium alloy ingots, having higher strength, ductility, toughness, and thermal stability.

[0013] Furthermore, the ultra-lightweight, high-strength, tough, and heat-resistant aluminum-magnesium alloy ingot has a tensile strength ≥369MPa, a yield strength ≥280MPa, an elongation ≥4.6%, a Vickers hardness ≥95HV, and a density ≤2.54g / cm³.

[0014] A second aspect of the present invention provides a method for preparing the above-mentioned ultralight, high-strength, tough, and heat-resistant aluminum-magnesium alloy ingot, comprising the following steps: Prepare raw materials according to the above-mentioned proportions for ultra-lightweight, high-strength, tough, and heat-resistant aluminum-magnesium alloy ingots. The raw materials include pure Al blocks, pure Mg blocks, Al-Sc master alloy, Al-Zr master alloy, and Al powder. Powder and TiC powder; The Al powder, the The powder and the TiC powder were ball-milled to obtain ( Composite ball milling particles; Under inert gas protection, the pure Al block is first melted at 740℃-760℃, then heated to 760℃-780℃, the Al-Sc master alloy and the Al-Zr master alloy are added for a second melt, then cooled to 700℃-720℃, the pure Mg block is added for a third melt, and then refined to obtain an alloy melt. The ( The composite ball milling particles are introduced into the alloy melt in an aluminum foil-wrapped manner for a first stirring, then cooled to 660℃-680℃ and held for 5-10 minutes, followed by a second stirring, casting, and cooling to obtain an ultra-light, high-strength, tough, and heat-resistant aluminum-magnesium alloy ingot.

[0015] Compared with the prior art, the preparation method of ultralight, high-strength, tough, and heat-resistant aluminum-magnesium alloy ingots provided by this invention has the following beneficial effects: First, by processing Al powder, The powder and TiC powder were ball-milled for effective crushing. The original agglomerates of TiC achieve uniform pre-dispersion of particles and interface activation; ball milling yields ( The composite ball milling particles, with Al as a continuous shell coating the ceramic phase, significantly improve the wettability of the ceramic particles with the aluminum melt, solving the technical problem of easy agglomeration and difficulty in dispersion of traditional added particles. After the composite ball milling particles are added to the matrix, they are uniformly dispersed. First, TiC particles act as heterogeneous nucleation cores for α-Al, refining the grain size. Second, they synergistically enhance the material's strength and thermal stability through load transfer and dislocation pinning effects. Third, this invention employs a specific melting sequence: first, pure Al blocks and Al-Sc and Al-Zr master alloys are melted to ensure complete solid solution of Sc and Zr; then, pure Mg blocks are added at a lower temperature to reduce the oxidation loss rate of Mg and improve the melt's resistance to oxidation. The wettability of TiC was assessed, and finally, composite ball-milled particles were introduced and held at 660℃-680℃ for 5-10 minutes. This process window ensured both the complete melting of the Al shell and the uniform release of particles, while effectively suppressing [the formation of harmful substances]. The formation of harmful interfacial reaction products between TiC and the aluminum matrix was reduced, and the original morphology of the particles was maintained. Third, a single stirring action promoted (…). The initial dispersion of composite ball-milled particles and the rapid melting and release of the Al shell, followed by secondary stirring, further improve the situation. The good dispersibility of TiC in the melt effectively suppresses the floating and settling agglomeration of ceramic particles, ensuring a uniform and dispersed distribution of the reinforcing phase in the final ingot. The synergistic effect of this specific melting sequence and the ball milling pre-dispersion process significantly improves the material's strength, thermal stability, and plasticity. Compared to existing technologies using rapid solidification powder metallurgy and additive manufacturing methods, this invention employs conventional gravity casting, which is low-cost, simple, and has significant economic benefits and practical engineering application potential.

[0016] Furthermore, the Sc content in the Al-Sc master alloy is 2wt.%-5wt.%; and the Zr content in the Al-Zr master alloy is 5wt.%-10wt.%.

[0017] Furthermore, the Al powder, the The powder and the TiC powder were ball-milled under inert gas protection conditions. The ball milling temperature was 10℃-30℃, the ball milling speed was 200r / min-300r / min, and the ball-to-material ratio was (9-20):1.

[0018] In this invention, when the ball milling temperature, rotation speed, and ball-to-material ratio meet the above-mentioned ranges, the dispersion effect of the composite ball milled particles can be further improved, while avoiding... , The formation of brittle phases.

[0019] Furthermore, during the first smelting, the second smelting, and the third smelting, a covering agent is added to the surface of the smelted metal; the covering agent is a mixture of magnesium chloride, potassium chloride, and calcium fluoride; the mass ratio is (2-3):(2-3):1, and the amount added is 3%-4% of the total raw material mass.

[0020] In this invention, when the composition and ratio of the covering agent, as well as the amount of covering agent added, meet the above-mentioned range, the covering agent can form a protective layer on the surface of the molten alloy liquid, effectively preventing oxidation and avoiding metal burn-off.

[0021] Furthermore, the refining temperature is 700℃-720℃.

[0022] Furthermore, the refining agent used in the refining process is a mixture of magnesium chloride, potassium chloride and calcium fluoride in a mass ratio of (1-2):(1-2):2, and the amount added is 3%-4% of the total raw material mass.

[0023] In this invention, when the composition and proportion of the refining agent meet the above-mentioned limitations, the refining agent can adsorb and remove non-metallic impurities in the melt, thereby improving the purity of the melt.

[0024] Furthermore, the (Al- The TiC composite ball milling particles are introduced into the alloy melt in an aluminum foil-wrapped manner. The temperature during the first stirring is 700℃-720℃, and the stirring speed is 150rpm-200rpm. Then, the temperature is lowered to 660℃-680℃ and held for 5min-10min. Then, a second stirring is performed, and the stirring speed is 150rpm-200rpm.

[0025] In this invention, when the temperature of the first stirring, the stirring speed, the heat preservation time after cooling, and the stirring speed of the second stirring meet the above ranges, it can be ensured that the composite ball milling particles are uniformly distributed in the aluminum matrix, which is beneficial to improving the strength, thermal stability and plasticity of the material.

[0026] Furthermore, after the secondary stirring, casting, and cooling, and before obtaining the ultralight aluminum-magnesium alloy ingot, a homogenization heat treatment and water quenching cooling step is included; wherein, the homogenization heat treatment temperature is 360℃-430℃, and the holding time is 15h-20h.

[0027] In this invention, the homogenization heat treatment pre-introduced... TiC particles can be used as The heterogeneous nucleation substrate of the phase promotes its uniform and dispersed precipitation, thereby inducing α-Al grain refinement and forming " → The two-step nucleation mechanism of α-Al further refines the grains; at the same time, homogenization treatment reduces residual coarse grains. Phase re-dissolution avoids damage to plasticity caused by continuous precipitation along the grain.

[0028] The third aspect of the present invention provides an ultralight, high-strength, tough, and heat-resistant aluminum-magnesium alloy sheet, wherein the ultralight, high-strength, tough, and heat-resistant aluminum-magnesium alloy ingot prepared by the above-mentioned ultralight, high-strength, tough, and heat-resistant aluminum-magnesium alloy ingot or the above-mentioned method for preparing ultralight, high-strength, tough, and heat-resistant aluminum-magnesium alloy ingot is subjected to multiple hot rolling passes to obtain the ultralight, high-strength, tough, and heat-resistant aluminum-magnesium alloy sheet.

[0029] In this invention, by performing multi-pass hot rolling on ultra-lightweight, high-strength, tough, and heat-resistant aluminum-magnesium alloy ingots, the small amount of undissolved material remaining in the ingots is eliminated. The phases are further broken down and dispersed, completely eliminating residual intergranular continuous network structure; at the same time, the grain structure is refined and the composition uniformity is improved through multiple hot rolling passes, which synergistically enhances the plasticity and thermal stability of the plate.

[0030] Furthermore, the rolling temperature of the multi-pass hot rolling is 410℃~430℃, and the total reduction rate is 70%-90%.

[0031] In this invention, when the rolling temperature and total reduction ratio meet the above-mentioned ranges, the grain size can be significantly refined and dislocation multiplication induced, while suppressing… The re-precipitation of the phase is beneficial to improving the strength, thermal stability and plasticity of the sheet.

[0032] Furthermore, the ultra-lightweight, high-strength, tough, and heat-resistant aluminum-magnesium alloy sheet has a tensile strength ≥670MPa, a yield strength ≥517MPa, an elongation ≥18%, and a Vickers hardness ≥180HV.

[0033] Furthermore, after being heat-treated at 300℃ for 1 hour, the ultra-lightweight, high-strength, tough, and heat-resistant aluminum-magnesium alloy sheet exhibits a tensile strength ≥560 MPa, a yield strength ≥433 MPa, an elongation ≥15.7%, and a Vickers hardness ≥150 HV. Attached Figure Description

[0034] The accompanying drawings, which are included to provide a further understanding of the invention and form part of this invention, illustrate exemplary embodiments of the invention and are used to explain the invention, but do not constitute an undue limitation of the invention. In the drawings: Figure 1 The fracture surface diagram is shown for the ultralight, high-strength, tough, and heat-resistant aluminum-magnesium alloy ingot (without homogenization heat treatment) of Example 1. Figure 2 The fracture surface diagram is shown in Example 7, which is an ultra-lightweight, high-strength, tough, and heat-resistant aluminum-magnesium alloy ingot after homogenization heat treatment. Figure 3 The fracture surface diagram is shown for the ultralight, high-strength, tough, and heat-resistant aluminum-magnesium alloy sheet #1 of Experimental Example 1. Detailed Implementation

[0035] To make the technical problems, technical solutions, and beneficial effects of this invention clearer, the invention will be further described in detail below with reference to embodiments. It should be understood that the specific embodiments described herein are merely illustrative and not intended to limit the invention.

[0036] Furthermore, the terms "first" and "second" are used for descriptive purposes only and should not be construed as indicating or implying relative importance or implicitly specifying the number of technical features indicated. Thus, a feature defined with "first" or "second" may explicitly or implicitly include one or more of that feature.

[0037] The first aspect of this invention provides an ultralight, high-strength, high-toughness, and heat-resistant aluminum-magnesium alloy ingot, wherein, by mass percentage, the ultralight, high-strength, high-toughness, and heat-resistant aluminum-magnesium alloy ingot comprises the following components: Mg: 7%-11%, Sc: 0.1%-0.4%, Zr: 0.1%-0.3%, (… Composite ball milling particles: 1.5%-2.5%, balance being Al and unavoidable impurities; Among them, the ( The composite ball milling particles contain Al powder, Powder and TiC powder.

[0038] Using the above-described embodiments, the amount of Mg added to the ultralight, high-strength, tough, and heat-resistant aluminum-magnesium alloy ingot is 7wt%-11wt%, which significantly improves the matrix strength through solid solution strengthening while maintaining the low-density characteristics of the aluminum alloy; Sc and Zr work synergistically to form nanoscale [structures] during the subsequent homogenization heat treatment process. Dispersed phases effectively pin grain boundaries, inhibit recrystallization, and improve the thermal stability of materials; After high-energy ball milling, the Al matrix shell of the composite ball milled particles preferentially melts during smelting, thus... TiC particles are uniformly released into the aluminum matrix, forming a "pre-dispersion-slow release-uniform distribution" mechanism, which enables... The TiC particles are uniformly dispersed in the matrix without significant agglomeration, thus fully leveraging the Orowan strengthening, grain refinement strengthening, and thermal mismatch strengthening effects. The synergistic effect of these components results in aluminum-magnesium alloy ingots of this invention exhibiting high strength and ductility, while maintaining low density to meet lightweight requirements.

[0039] For example, in ultra-lightweight, high-strength, tough, and heat-resistant aluminum-magnesium alloy ingots, the amount of Mg added can be 7%, 8%, 9%, 9.5%, 10%, or 11% by mass; the amount of Sc added can be 0.1%, 0.2%, 0.25%, 0.3%, or 0.4%; and the amount of Zr added can be 0.1%, 0.15%, 0.2%, 0.25%, or 0.3%. The amount of composite ball milling particles added can be 1.5%, 2% or 2.5%, or any range consisting of two points; the balance is Al.

[0040] Preferably, based on the mass percentage of the ultralight, high-strength, tough, and heat-resistant aluminum-magnesium alloy ingot, the ultralight, high-strength, tough, and heat-resistant aluminum-magnesium alloy ingot comprises the following components: Mg: 9%-10%, Sc: 0.2%-0.3%, Zr: 0.2%-0.3%, ( Composite ball milling particles: 2%-2.5%, with the balance being Al and unavoidable impurities.

[0041] In some embodiments, the ( In the composite ball milled particles, the Al powder, the... The mass ratio of powder to TiC powder is (1-3):1:1.

[0042] Using the above implementation method, when Al powder, When the mass ratio of aluminum powder to TiC powder meets the above range, the ultralight, high-strength, tough, and heat-resistant aluminum-magnesium alloy ingot exhibits higher strength, thermal stability, and plasticity. For example, the (…) In the composite ball milled particles, the Al powder, the... The mass ratio of the powder to the TiC powder can be 1:1:1, 1.5:1:1, 2:1:1, 2.5:1:1, 3:1:1, or any two of the above ratios.

[0043] Preferably, the Al powder, the The mass ratio of powder to TiC powder is (2-3):1:1.

[0044] In some embodiments, the Al powder, the The average particle size of the powder and the TiC powder are each independently 1 μm-3 μm.

[0045] For example, Al powder, The average particle size of the powder and TiC powder can be 1 μm, 2 μm or 3 μm, or any range consisting of two point values.

[0046] Using the above implementation method, when Al powder, When the average particle size of the powder and TiC powder meets the above range, it is beneficial to further improve the dispersion uniformity of the composite ball milling particles, thereby improving the strength, thermal stability and plasticity of the material.

[0047] In some embodiments, the ultralight, high-strength, tough, and heat-resistant aluminum-magnesium alloy ingot has a tensile strength ≥369MPa, a yield strength ≥280MPa, an elongation ≥4.6%, a Vickers hardness ≥95HV, and a density ≤2.54g / cm³.

[0048] In some embodiments, the tensile strength of the unhomogenized ultra-lightweight, high-strength, tough, and heat-resistant aluminum-magnesium alloy ingot is ≥369 MPa, preferably 400-430 MPa; the yield strength is ≥280 MPa, preferably 300-320 MPa; the elongation is ≥4.6%, preferably 5-6%; and the Vickers hardness is ≥95 HV, preferably 100-110 HV. In other embodiments, the tensile strength of the homogenized heat-treated ultra-lightweight, high-strength, tough, and heat-resistant aluminum-magnesium alloy ingot is ≥420 MPa, preferably 435-470 MPa; the yield strength is ≥300 MPa, preferably 315-340 MPa; the elongation is ≥26%, preferably 26.5-32%; and the Vickers hardness is ≥115 HV, preferably 120-135 HV.

[0049] A second aspect of the present invention provides a method for preparing the above-mentioned ultralight, high-strength, tough, and heat-resistant aluminum-magnesium alloy ingot, comprising the following steps: Prepare raw materials according to the above-mentioned proportions for ultra-lightweight, high-strength, tough, and heat-resistant aluminum-magnesium alloy ingots. The raw materials include pure Al blocks, pure Mg blocks, Al-Sc master alloy, Al-Zr master alloy, and Al powder. Powder and TiC powder; The Al powder, the The powder and the TiC powder were ball-milled to obtain ( Composite ball milling particles; Under inert gas protection, the pure Al block is first melted at 740℃-760℃, then heated to 760℃-780℃, the Al-Sc master alloy and the Al-Zr master alloy are added for a second melt, then cooled to 700℃-720℃, the pure Mg block is added for a third melt, and then refined to obtain an alloy melt. The ( The composite ball milling particles are introduced into the alloy melt in an aluminum foil-wrapped manner for a first stirring, then cooled to 660℃-680℃ and held for 5-10 minutes, followed by a second stirring, casting, and cooling to obtain an ultra-light, high-strength, tough, and heat-resistant aluminum-magnesium alloy ingot.

[0050] Using the above-described implementation method, by processing Al powder, The powder and TiC powder were ball-milled to effectively break them down. The original aggregates of powder and TiC powder are realized. Uniform pre-dispersion and interfacial activation of particles and TiC particles in an aluminum matrix. Composite ball-milled particles, as micron-scale external reinforcing phases, are more easily dispersed in the aluminum matrix. On the one hand, they can act as heterogeneous nucleation sites, refining the grain size; on the other hand, they can effectively improve the tensile strength of lightweight, high-strength, and high-toughness high-magnesium aluminum alloys by bearing loads and hindering dislocation movement. Existing technologies mostly involve directly adding Ti powder and... Powder, generated through high-temperature in-situ reaction And TiC particles. However, this in-situ synthesis method is prone to generating at the interface. The reaction contains harmful phases, and the process is highly sensitive to melt temperature and stirring conditions, resulting in poor batch stability. Especially in high-magnesium alloy systems, the highly reactive Mg element can interfere with the thermodynamic equilibrium of the in-situ reaction, inhibiting... The formation of TiC or the resulting byproducts (e.g.) The generation of interfacial reactants makes it difficult to achieve a stable and controllable enhancement effect.

[0051] Furthermore, in the smelting process of this invention, pure Al blocks are first smelted at 740℃-760℃, and then heated to 760℃-780℃. Al-Sc master alloy and Al-Zr master alloy are then added for a second smelting, allowing Sc and Zr to fully dissolve in the aluminum matrix. This facilitates the preferential reaction of Sc and Zr with Al to form… The dispersed phase refines the grains, improving the strength and plasticity of the lightweight, high-strength, and high-toughness magnesium-aluminum alloy; subsequently, when the temperature is lowered to 700℃-720℃, pure Mg blocks are added for a third smelting process to reduce the oxidation loss rate of Mg and improve the wettability of the melt to ceramic particles, followed by refining to obtain the alloy melt; the (… The composite ball milling particles are introduced into the alloy melt in an aluminum foil-wrapped manner for a single stirring, and then cooled to 660℃-680℃ and held for 5-10 minutes. This reduces atomic activity and inhibits the formation of harmful interface products, thereby maintaining... The alloy melt exhibits complete micron-sized morphology and interfacial bonding strength with TiC particles; after heat preservation, it undergoes secondary stirring, casting, and cooling to obtain an ultralight, high-strength, tough, and heat-resistant aluminum-magnesium alloy ingot; primary stirring promotes initial particle dispersion, while secondary stirring further improves the properties of the melt. And the dispersion of TiC effectively reduces The floating and settling of TiC ensures uniform distribution within the aluminum matrix. The synergistic effect of the specific melting sequence and ball milling pre-dispersion process improves the strength, thermal stability, and plasticity of ultra-lightweight, high-strength, tough, and heat-resistant aluminum-magnesium alloy ingots and plates.

[0052] In addition, compared with existing technologies that use rapid solidification powder metallurgy and additive manufacturing methods, this invention uses ordinary gravity casting, which is low in cost, simple in process, and has significant economic benefits and potential for practical engineering applications.

[0053] It is understood that the Sc component in the ultra-lightweight, high-strength, tough, and heat-resistant aluminum-magnesium alloy ingot is introduced in the form of an Al-Sc master alloy; the Zr component is introduced in the form of an Al-Zr master alloy. The melting point of the Al-Sc master alloy is 650℃-670℃, and the melting point of the Al-Zr master alloy is 650℃-670℃.

[0054] In some embodiments, the Al-Sc master alloy contains 2 wt.%-5 wt.% Sc, with the balance being Al; the Al-Zr master alloy contains 5 wt.%-10 wt.% Zr, with the balance being Al.

[0055] For example, the Sc content in the Al-Sc master alloy can be 2 wt.%, 3 wt.%, 4 wt.%, or 5 wt.%, or any range consisting of any two of the above values. The Zr content in the Al-Zr master alloy can be 5 wt.%, 6 wt.%, 7 wt.%, 8 wt.%, 9 wt.%, or 10 wt.%, or any range consisting of any two of the above values.

[0056] Preferably, the Al-Sc master alloy has a Sc content of 2 wt.%-3 wt.%; and the Al-Zr master alloy has a Zr content of 5 wt.%-6 wt.%.

[0057] In some embodiments, the Al powder, the The Al powder and the TiC powder were ball-milled under inert gas protection conditions. The ball milling temperature was 10℃-30℃, the ball milling speed was 200r / min-300r / min, and the ball-to-material ratio was (9-20):1. The Al powder, the TiB2 powder, and the TiC powder were ball-milled under inert gas protection conditions for 1-3 hours.

[0058] For example, the ball mill temperature can be 10℃, 20℃, 25℃ or 30℃; the ball mill speed can be 200r / min, 250r / min or 300r / min; the ball-to-material ratio can be 9:1, 15:1 or 20:1; the ball milling time can be 1h, 2h or 3h; or any range consisting of two points.

[0059] Using the above implementation method, when Al powder, When the temperature, rotation speed, and ball-to-particle ratio of the TiC ball mill meet the above-mentioned ranges, the dispersion effect of the composite ball-milled particles in the aluminum matrix can be further improved, while avoiding... , The formation of brittle phases and the interference of side reactions on the formation of reinforcing phases in a high-magnesium environment are beneficial to improving the mechanical strength, plasticity and toughness of lightweight, high-strength and high-toughness high-magnesium aluminum alloys.

[0060] Preferably, the Al powder, the The powder and the TiC powder were ball-milled under inert gas protection conditions. The ball milling temperature was 20℃-30℃, the ball milling speed was 200r / min-250r / min, and the ball-to-material ratio was (15-20):1.

[0061] In some embodiments, Al powder, The inert gas used in the ball milling of powder and TiC powder, as well as the inert gas used in the first melting, second melting and third melting, is selected from at least one of argon and carbon dioxide, preferably argon.

[0062] In some embodiments, during the first smelting, the second smelting, and the third smelting, a covering agent is added to the surface of the smelted metal; the covering agent is a mixture of magnesium chloride, potassium chloride, and calcium fluoride; the mass ratio of magnesium chloride, potassium chloride, and calcium fluoride is (2-3):(2-3):1; and the amount of the covering agent added is 3%-4% of the total raw material mass.

[0063] For example, the mass ratio of magnesium chloride, potassium chloride and calcium fluoride can be 2:2:1, 2.5:2.5:1 or 3:3:1; the amount of covering agent added can be 3%, 3.5% or 4% of the total raw material mass.

[0064] Using the above embodiments, when the composition and ratio of the covering agent, as well as the amount of covering agent added, meet the above-mentioned ranges, the covering agent can form a protective layer on the surface of the molten alloy, effectively preventing oxidation of the molten alloy and avoiding metal burn-off. It is understood that the total raw material mass includes pure Al blocks, pure Mg blocks, Al-Sc master alloy, Al-Zr master alloy, Al powder, etc. The total mass of powder and TiC powder.

[0065] In some embodiments, the first melting time is 30-40 minutes. The second melting time is 30-40 minutes. The third melting time is 20-30 minutes.

[0066] In some embodiments, the refining temperature is 700℃-720℃. The refining time is 5min-10min.

[0067] For example, the refining temperature can be 700°C, 710°C, or 720°C, or a range consisting of any two point values.

[0068] Preferably, the refining temperature is 710℃-720℃.

[0069] In some embodiments, the refining agent used during refining is a mixture of magnesium chloride, potassium chloride and calcium fluoride, wherein the mass ratio of magnesium chloride, potassium chloride and calcium fluoride is (0.5-1):(0.5-1):1; and the amount of refining agent added is 3%-4% of the total raw material mass.

[0070] For example, the mass ratio of magnesium chloride, potassium chloride, and calcium fluoride can be 0.5:0.5:1, 0.75:0.75:1, or 1:1:1; the amount of refining agent added can be 3%, 3.5%, or 4% of the total raw material mass, or any range consisting of two points.

[0071] Using the above-described embodiments, when the composition and proportion of the refining agent meet the aforementioned limitations, the refining agent can adsorb non-metallic impurities in the alloy melt and remove these impurities through conventional slag removal methods, thereby improving the purity of the alloy melt. Furthermore, when the amount of refining agent added meets the aforementioned range, non-metallic impurities in the alloy melt can be sufficiently removed, ensuring the purity of the final alloy obtained.

[0072] Preferably, the mass ratio of the magnesium chloride, the potassium chloride and the calcium fluoride is (0.5-0.75):(0.5-0.75):1; and the amount of the refining agent added is 3.5%-4% of the total raw material mass.

[0073] In some embodiments, the ( The composite ball milling particles are introduced into the alloy melt in an aluminum foil-wrapped manner. The initial stirring temperature is 700℃-720℃, and the stirring speed is 150rpm-200rpm. The temperature is then lowered to 660℃-680℃ and held for 5-10 minutes. A second stirring is then performed at 150rpm-200rpm. The initial stirring time is 1-2 minutes, and the second stirring time is also 1-2 minutes.

[0074] For example, the temperature during the first stirring can be 700℃, 710℃, or 720℃; the stirring speed during the first stirring can be 150rpm, 180rpm, or 200rpm; then the temperature is lowered to 660℃, 670℃, or 680℃ and held for 5min, 7min, or 10min; then the stirring speed during the second stirring can be 150rpm, 180rpm, or 200rpm.

[0075] By adopting the above-described embodiments, when the temperature of the first stirring, the stirring speed, the holding time after cooling, and the stirring speed of the second stirring meet the above-described ranges, the composite ball milling particles can be evenly distributed in the aluminum matrix, which is beneficial to improving the strength, thermal stability, and plasticity of the material.

[0076] Preferably, the ( The composite ball milling particles are introduced into the alloy melt in an aluminum foil-wrapped manner. The temperature during the first stirring is 710℃-720℃, and the stirring speed during the first stirring is 170rpm-200rpm. The temperature is then lowered to 670℃-680℃ and held for 7min-10min. The stirring speed during the second stirring is 170rpm-200rpm.

[0077] In other embodiments, after secondary stirring, casting, and cooling, and before obtaining the ultralight aluminum-magnesium alloy ingot, a homogenization heat treatment and water quenching cooling step is further included; wherein, the homogenization heat treatment temperature is 360℃-430℃, and the holding time is 15h-20h.

[0078] For example, the homogenization heat treatment temperature can be 360℃, 370℃, 380℃, 390℃, 400℃, 410℃, 420℃ or 430℃; the holding time can be 15h, 16h, 17h, 18h, 19h or 20h, or any range consisting of two point values.

[0079] The third aspect of the present invention provides an ultralight, high-strength, tough, and heat-resistant aluminum-magnesium alloy sheet, wherein the ultralight, high-strength, tough, and heat-resistant aluminum-magnesium alloy ingot prepared by the above-mentioned ultralight, high-strength, tough, and heat-resistant aluminum-magnesium alloy ingot or the above-mentioned method for preparing ultralight, high-strength, tough, and heat-resistant aluminum-magnesium alloy ingot is subjected to multiple hot rolling passes to obtain the ultralight, high-strength, tough, and heat-resistant aluminum-magnesium alloy sheet.

[0080] In some embodiments, the rolling temperature of the multi-pass hot rolling is 410°C to 430°C, and the total reduction rate is 70% to 90%.

[0081] For example, the rolling temperature of multi-pass hot rolling can be 410°C, 415°C or 430°C; the total reduction rate can be 70%, 80% or 90%, or a range consisting of any two point values.

[0082] By employing the above-described embodiments, multi-pass hot rolling of ultralight, high-strength, tough, and heat-resistant aluminum-magnesium alloy ingots can significantly refine grain size and induce dislocation proliferation, while suppressing… The re-precipitation of the phase effectively avoids intergranular continuous network precipitation, which is beneficial to improving the plasticity and thermal stability of the plate.

[0083] In some embodiments, the ultralight, high-strength, tough, and heat-resistant aluminum-magnesium alloy sheet has a tensile strength ≥670MPa, a yield strength ≥517MPa, an elongation ≥18%, and a Vickers hardness ≥180HV.

[0084] Preferably, the ultralight, high-strength, tough, and heat-resistant aluminum-magnesium alloy sheet has a tensile strength of 690-725 MPa, a yield strength of 525-550 MPa, an elongation of 18.8-20%, and a Vickers hardness of 185-200 HV.

[0085] In some embodiments, after the ultra-lightweight, high-strength, tough, and heat-resistant aluminum-magnesium alloy sheet is heat-treated at 300°C for 1 hour, the tensile strength is ≥560 MPa, the yield strength is ≥433 MPa, the elongation is ≥15.7%, and the Vickers hardness is ≥150 HV.

[0086] Preferably, after heat treatment at 300℃ for 1 hour, the ultra-lightweight, high-strength, tough, and heat-resistant aluminum-magnesium alloy sheet has a tensile strength of 560MPa-610MPa, a yield strength of 433MPa-460MPa, an elongation of 15.7%-17%, and a Vickers hardness of 150HV-175HV.

[0087] To better illustrate the technical solution of the present invention, the following specific embodiments are also provided.

[0088] In the following examples and comparative examples, the particle size of the Al powder is 1-3 μm; The particle size of the powder is 1-3 μm; the average particle size of TiC powder is 1 μm. The melting point of the Al-Sc master alloy is 650-670℃, and the Sc content is 2wt.%; the melting point of the Al-Zr master alloy is 650-670℃, and the Zr content is 5wt.%.

[0089] Test methods for yield strength, tensile strength and elongation of lightweight, high-strength and tough high-magnesium aluminum alloy: The dumbbell-shaped specimens of lightweight, high-strength and tough high-magnesium aluminum alloy were subjected to tensile tests at a tensile rate of 0.5 mm / min at room temperature using an Instron 5969 universal tensile testing machine. The strength and toughness of the material were characterized by the stress-strain curve and tensile fracture morphology. Three samples of the same type of material were tested in each example and comparative example, and the average value of each property was calculated.

[0090] Specific strength: Specific strength is the ratio of tensile strength to apparent density. Tensile strength is obtained by testing as described above. Sample density is determined using Archimedes' water displacement method as specified in GB / T 3850-2015. After cleaning and drying, the sample is weighed in air using an analytical balance with a sensitivity of not less than 0.1 mg. The sample was suspended and completely immersed in distilled water using a thin wire with a diameter ≤0.25 mm. After removing any attached air bubbles, the apparent mass in the water was measured. The test temperature was controlled at (20±2)℃, and the density of distilled water was... The value is taken as 0.9982 g / cm³ (at 20℃). Density is calculated using the formula... The density of the sample was calculated, and the average value of the three measurements was taken as the sample density.

[0091] Hardness of lightweight, high-strength, and tough high-magnesium aluminum alloy: The Vickers hardness of the alloy was tested using an HVS-1000 microhardness tester. The load used in the experiment was 300g, and the holding time was 15s. Before the test, the upper and lower surfaces of the sample were sanded and mechanically polished to ensure that each sample had the same roughness. Ten points were tested on each sample in different areas, and the final hardness of the sample was the average of the hardness values ​​of the ten points.

[0092] Example 1 This embodiment provides an ultralight, high-strength, high-toughness, and heat-resistant aluminum-magnesium alloy ingot. Based on the mass percentage of the ultralight, high-strength, high-toughness, and heat-resistant aluminum-magnesium alloy ingot, the ingot comprises the following components: Mg: 10%, Sc: 0.2%, Zr: 0.2%, ( Composite ball milled particles: 2%, balance Al; Al powder in composite ball milled particles, The mass ratio of powder to TiC powder is 2:1:1; The preparation method of the ultralight, high-strength, tough, and heat-resistant aluminum-magnesium alloy ingot in this embodiment includes the following steps: S1. Prepare raw materials according to the above-mentioned proportions for ultra-lightweight, high-strength, tough, and heat-resistant aluminum-magnesium alloy ingots. The raw materials include pure Al blocks, pure Mg blocks, Al-Sc master alloy, Al-Zr master alloy, and Al powder. Powder and TiC powder; the surfaces of pure Al blocks, pure Mg blocks, Al-Sc master alloys, and Al-Zr master alloys are ground with a grinding wheel at a speed of 1000 rpm. After grinding, they are cleaned with anhydrous ethanol and dried at 200°C for later use. S2. Al powder, TiB2 powder and TiC powder were ball-milled for 2 hours under argon protection at 25℃. The ball milling speed was 250 r / min and the ball-to-material ratio was 15:1 to obtain composite ball-milled particles. S3. Under argon protection, the graphite crucible is placed in an electric resistance furnace and heated to 760°C. The polished pure Al block is placed in the crucible, and after adding a covering agent, it is melted for 30 minutes and then the slag is removed. The covering agent is a mixture of magnesium chloride, potassium chloride and calcium fluoride in a mass ratio of 2:2:1, and the amount of covering agent added is 3.5% of the total raw material mass. The graphite crucible is heated to 780℃, Al-Sc master alloy and Al-Zr master alloy are added, and then 3.5% of the total raw material mass of covering agent is added. After melting for 30 minutes, the slag is removed. The graphite crucible was cooled to 720℃, pure Mg blocks were added, and then 3.5% of the total raw material mass of the covering agent was added. After melting for 30 minutes, the slag was removed, and then a refining agent was added. The refining agent was a mixture of magnesium chloride, potassium chloride and calcium fluoride in a mass ratio of 0.75:0.75:1. The amount of refining agent added was 3.5% of the total raw material mass. After refining for 10 minutes, the slag was removed to obtain the alloy melt. S4. At 720℃, the composite ball milling particles were introduced into the alloy melt by wrapping them in aluminum foil. A bell jar was used to press the composite ball milling particles below the surface of the alloy liquid until it melted, and the mixture was stirred once at a speed of 200 rpm for 1 min. The temperature was then lowered to 680℃ and held for 10 min, followed by a second stirring at a speed of 200 rpm for 1 min. Slag was removed, and the mixture was cast into a cylindrical copper mold under argon protection. After cooling, an ultralight, high-strength, high-toughness, and heat-resistant aluminum-magnesium alloy ingot was obtained. The performance test results of the ultralight, high-strength, high-toughness, and heat-resistant aluminum-magnesium alloy ingot are shown in Table 1.

[0093] Example 2 This embodiment provides an ultralight, high-strength, high-toughness, and heat-resistant aluminum-magnesium alloy ingot. Based on the mass percentage of the ultralight, high-strength, high-toughness, and heat-resistant aluminum-magnesium alloy ingot, the ingot comprises the following components: Mg: 7%, Sc: 0.1%, Zr: 0.1%, ( Composite ball milled particles: 1.5%, balance Al; Al powder in composite ball milled particles, The mass ratio of powder to TiC powder is 1:1:1; The preparation method of the ultralight, high-strength, tough, and heat-resistant aluminum-magnesium alloy ingot in this embodiment includes the following steps: S1. Prepare raw materials according to the above-mentioned proportions for ultra-lightweight, high-strength, tough, and heat-resistant aluminum-magnesium alloy ingots. The raw materials include pure Al blocks, pure Mg blocks, Al-Sc master alloy, Al-Zr master alloy, and Al powder. Powder and TiC powder; the surfaces of pure Al blocks, pure Mg blocks, Al-Sc master alloys, and Al-Zr master alloys are ground with a grinding wheel at a speed of 1000 rpm. After grinding, they are cleaned with anhydrous ethanol and dried at 200°C for later use. S2, At 25℃, Al powder, Powder and TiC powder were ball-milled for 1 hour under argon protection. The ball milling speed was 300 r / min and the ball-to-powder ratio was 9:1 to obtain composite ball-milled particles. S3. Under argon protection, the graphite crucible is placed in an electric resistance furnace and heated to 740°C. The polished pure Al block is placed in the crucible, and after adding a covering agent, it is melted for 30 minutes and then the slag is removed. The covering agent is a mixture of magnesium chloride, potassium chloride and calcium fluoride in a mass ratio of 2.5:2.5:1, and the amount of covering agent added is 3% of the total raw material mass. The graphite crucible is heated to 760℃, Al-Sc master alloy and Al-Zr master alloy are added, and then a covering agent of 3% of the total raw material mass is added. After melting for 30 minutes, the slag is removed. The graphite crucible was cooled to 700℃, pure Mg blocks were added, and then 3% of the total raw material mass of covering agent was added. After melting for 30 minutes, the slag was removed, and then a refining agent was added. The refining agent was a mixture of magnesium chloride, potassium chloride and calcium fluoride in a mass ratio of 0.5:0.5:1. The amount of refining agent added was 3% of the total raw material mass. After refining for 10 minutes, the slag was removed to obtain the alloy melt. S4. At 700℃, the composite ball milling particles were introduced into the alloy melt by wrapping them in aluminum foil. A bell jar was used to press the composite ball milling particles below the surface of the alloy liquid until it melted, and the mixture was stirred once at a speed of 200 rpm for 1 min. The temperature was then lowered to 660℃ and held for 5 min, followed by a second stirring at a speed of 200 rpm for 1 min. Slag was removed, and the mixture was cast into a cylindrical copper mold under argon protection. After cooling, an ultralight, high-strength, high-toughness, and heat-resistant aluminum-magnesium alloy ingot was obtained. The performance test results of the ultralight, high-strength, high-toughness, and heat-resistant aluminum-magnesium alloy ingot are shown in Table 1.

[0094] Example 3 This embodiment provides an ultralight, high-strength, high-toughness, and heat-resistant aluminum-magnesium alloy ingot. Based on the mass percentage of the ultralight, high-strength, high-toughness, and heat-resistant aluminum-magnesium alloy ingot, the ingot comprises the following components: Mg: 9.5%, Sc: 0.3%, Zr: 0.3%, ( Composite ball milled particles: 2.5%, balance Al; Al powder in composite ball milled particles, The mass ratio of powder to TiC powder is 3:1:1; The preparation method of the ultralight, high-strength, tough, and heat-resistant aluminum-magnesium alloy ingot in this embodiment includes the following steps: S1. Prepare raw materials according to the above-mentioned proportions for ultra-lightweight, high-strength, tough, and heat-resistant aluminum-magnesium alloy ingots. The raw materials include pure Al blocks, pure Mg blocks, Al-Sc master alloy, Al-Zr master alloy, and Al powder. Powder and TiC powder; the surfaces of pure Al blocks, pure Mg blocks, Al-Sc master alloys, and Al-Zr master alloys are ground with a grinding wheel at a speed of 1000 rpm. After grinding, they are cleaned with anhydrous ethanol and dried at 200°C for later use. S2, At 25℃, Al powder, Powder and TiC powder were ball-milled for 3 hours under argon protection. The ball milling speed was 200 r / min and the ball-to-powder ratio was 20:1 to obtain composite ball-milled particles. S3. Under argon protection, the graphite crucible is placed in an electric resistance furnace and heated to 750°C. The polished pure Al block is placed in the crucible, and after adding a covering agent, it is melted for 30 minutes and then the slag is removed. The covering agent is a mixture of magnesium chloride, potassium chloride and calcium fluoride in a mass ratio of 3:3:1, and the amount of covering agent added is 4% of the total raw material mass. The graphite crucible was heated to 770℃, Al-Sc master alloy and Al-Zr master alloy were added, and then 4% of the total raw material mass of covering agent was added. After melting for 30 minutes, the slag was removed. The graphite crucible was cooled to 710℃, pure Mg blocks were added, and then 4% of the total raw material mass of the covering agent was added. After melting for 30 minutes, the slag was removed, and then the refining agent was added. The refining agent was a mixture of magnesium chloride, potassium chloride and calcium fluoride in a mass ratio of 1:1:1. The amount of refining agent added was 4% of the total raw material mass. After refining for 10 minutes, the slag was removed to obtain the alloy melt. S4. At 710℃, the composite ball milling particles were introduced into the alloy melt by wrapping them in aluminum foil. A bell jar was used to press the composite ball milling particles below the surface of the alloy liquid until it melted, and the mixture was stirred once at a speed of 200 rpm for 1 min. The temperature was then lowered to 670℃ and held for 10 min, followed by a second stirring at a speed of 200 rpm for 1 min. Slag was removed, and the mixture was cast into a cylindrical copper mold under argon protection. After cooling, an ultralight, high-strength, high-toughness, and heat-resistant aluminum-magnesium alloy ingot was obtained. The performance test results of the ultralight, high-strength, high-toughness, and heat-resistant aluminum-magnesium alloy ingot are shown in Table 1.

[0095] Example 4 This embodiment provides an ultralight, high-strength, high-toughness, and heat-resistant aluminum-magnesium alloy ingot. Based on the mass percentage of the ultralight, high-strength, high-toughness, and heat-resistant aluminum-magnesium alloy ingot, the ingot comprises the following components: Mg: 10%, Sc: 0.25%, Zr: 0.15%, ( Composite ball milled particles: 2%, balance Al; Al powder in composite ball milled particles, The mass ratio of powder to TiC powder is 1.5:1:1.

[0096] The preparation method of the ultralight, high-strength, tough, and heat-resistant aluminum-magnesium alloy ingot in this embodiment is the same as that in Example 1. The performance test results of the obtained ultralight, high-strength, tough, and heat-resistant aluminum-magnesium alloy ingot are shown in Table 1.

[0097] Example 5 This embodiment provides an ultralight, high-strength, high-toughness, and heat-resistant aluminum-magnesium alloy ingot. Based on the mass percentage of the ultralight, high-strength, high-toughness, and heat-resistant aluminum-magnesium alloy ingot, the ingot comprises the following components: Mg: 10%, Sc: 0.2%, Zr: 0.2%, ( Composite ball milled particles: 2%, balance Al; Al powder in composite ball milled particles, The mass ratio of powder to TiC powder is 0.5:1:1.

[0098] The preparation method of the ultralight, high-strength, tough, and heat-resistant aluminum-magnesium alloy ingot in this embodiment is the same as that in Example 1. The performance test results of the obtained ultralight, high-strength, tough, and heat-resistant aluminum-magnesium alloy ingot are shown in Table 1.

[0099] Example 6 This embodiment provides an ultralight, high-strength, high-toughness, and heat-resistant aluminum-magnesium alloy ingot. Based on the mass percentage of the ultralight, high-strength, high-toughness, and heat-resistant aluminum-magnesium alloy ingot, the ingot comprises the following components: Mg: 10%, Sc: 0.2%, Zr: 0.2%; composite milled particles: 2%, balance Al; Al powder in the composite milled particles... The mass ratio of powder to TiC powder is 2:2:1.

[0100] The preparation method of the ultralight, high-strength, tough, and heat-resistant aluminum-magnesium alloy ingot in this embodiment is the same as that in Example 1. The performance test results of the obtained ultralight, high-strength, tough, and heat-resistant aluminum-magnesium alloy ingot are shown in Table 1.

[0101] Comparative Example 1 This comparative example provides an ultralight, high-strength, tough, and heat-resistant aluminum-magnesium alloy ingot. The difference from Example 1 is that the composite ball-milled particles are replaced with an equal mass ratio of Al powder. The raw materials used were powder and TiC powder; the types and amounts of the remaining raw materials were the same as in Example 1. The performance test results of the obtained ultralight, high-strength, tough, and heat-resistant aluminum-magnesium alloy ingots are shown in Table 1.

[0102] Comparative Example 2 This comparative example provides an ultralight, high-strength, tough, and heat-resistant aluminum-magnesium alloy ingot. The difference from Example 1 is that the composite ball milling particles do not contain... The powder was replaced with an equal mass of TiC powder. The mass ratio of Al powder to TiC powder was 1:1; the types and amounts of other raw materials were the same as in Example 1. The performance test results of the obtained ultralight, high-strength, tough, and heat-resistant aluminum-magnesium alloy ingot are shown in Table 1.

[0103] Comparative Example 3 This comparative example provides an ultralight, high-strength, tough, and heat-resistant aluminum-magnesium alloy ingot. The difference from Example 1 is that the composite ball-milled particles do not contain TiC powder and are made from equal masses. Replace TiC powder with Al powder and The powder mass ratio was 1:1; the types and amounts of other raw materials were the same as in Example 1. The performance test results of the obtained ultralight, high-strength, tough, and heat-resistant aluminum-magnesium alloy ingot are shown in Table 1.

[0104] Comparative Example 4 This comparative example provides an ultralight, high-strength, tough, and heat-resistant aluminum-magnesium alloy ingot. The difference from Example 1 is that the composite ball-milled particles do not contain Al powder. The mass ratio of aluminum powder to TiC powder was 1:1; the types and amounts of other raw materials were the same as in Example 1. The performance test results of the obtained ultralight, high-strength, tough, and heat-resistant aluminum-magnesium alloy ingot are shown in Table 1.

[0105] Comparative Example 5 This comparative example provides an ultralight, high-strength, tough, and heat-resistant aluminum-magnesium alloy ingot. The difference from Example 1 is that the amount of Sc added in the ultralight, high-strength, tough, and heat-resistant aluminum-magnesium alloy ingot is 0, while the amount of Zr added is increased to 0.4%. The types and amounts of the remaining raw materials are the same as in Example 1. The performance test results of the obtained ultralight, high-strength, tough, and heat-resistant aluminum-magnesium alloy ingot are shown in Table 1.

[0106] Comparative Example 6 This comparative example provides an ultralight, high-strength, tough, and heat-resistant aluminum-magnesium alloy ingot. The composition of the ultralight, high-strength, tough, and heat-resistant aluminum-magnesium alloy ingot in this comparative example is the same as that in Example 1.

[0107] The preparation method of the ultralight, high-strength, tough, and heat-resistant aluminum-magnesium alloy ingot in this comparative example is the same as that in Example 1, except that: S3. Under argon protection, a graphite crucible was placed in an electric resistance furnace and heated to 760°C. Pure Al blocks, pure Mg blocks, Al-Sc master alloy, and Al-Zr master alloy were placed in the crucible. After adding a covering agent, the mixture was melted for 90 minutes, and then the slag was removed. The covering agent was a mixture of magnesium chloride, potassium chloride, and calcium fluoride in a mass ratio of 2:2:1, and the amount of covering agent added was 4% of the total raw material mass. Then, a refining agent was added. The refining agent was a mixture of magnesium chloride, potassium chloride, and calcium fluoride in a mass ratio of 0.75:0.75:1, and the amount of refining agent added was 4% of the total raw material mass. After refining for 10 minutes, the slag was removed to obtain the alloy melt. The performance test results of the obtained ultralight, high-strength, tough, and heat-resistant aluminum-magnesium alloy ingot are shown in Table 1. The fracture diagram of the ultralight, high-strength, tough, and heat-resistant aluminum-magnesium alloy ingot of Example 1 is shown below. Figure 1 As shown.

[0108] Table 1. Performance test results of ultralight, high-strength, tough, and heat-resistant aluminum-magnesium alloy ingots (without homogenization heat treatment) As can be seen from Table 1, the yield strength, tensile strength, elongation, hardness, and specific strength of the ultralight, high-strength, high-toughness, and heat-resistant aluminum-magnesium alloy ingots prepared in Examples 1-6 of this invention are significantly better than those of the ultralight, high-toughness, and heat-resistant aluminum-magnesium alloy ingots in Comparative Examples 1-6, indicating that the addition of a specific content of ( Composite ball-milled particles, synergistically supplemented with specific amounts of Sc and Zr elements, can significantly improve the comprehensive mechanical properties of ultralight, high-strength, toughness, and heat-resistant aluminum-magnesium alloy ingots, particularly their strength and toughness. Furthermore, by adding (Sc and Zr elements to the Al-Mg alloy...) Composite ball-milled particles, through ball milling pre-dispersion and smelting stirring processes, can be made... The dispersed distribution of TiC micron-sized particles in the ultralight, high-strength, tough, and heat-resistant aluminum-magnesium alloy ingot promotes grain refinement and significantly improves the overall performance of the ingot. Furthermore, the Sc and Zr elements in the ingot form a dispersed distribution with the Al matrix. Nano-precipitated phase, The phase effectively pins grain boundaries and inhibits recrystallization, resulting in precipitation strengthening. TiC micron particles and The plates made from the ultra-lightweight, high-strength, tough, and heat-resistant aluminum-magnesium alloy ingots of this invention exhibit excellent mechanical properties due to their synergistic effect in hindering dislocation movement.

[0109] Examples 7-12 The ultralight, high-strength, tough, and heat-resistant aluminum-magnesium alloy ingots from Examples 1-6 were respectively applied to Examples 7-12 to prepare ultralight, high-strength, tough, and heat-resistant aluminum-magnesium alloy ingots after homogenization heat treatment.

[0110] The specific preparation method of the ultralight, high-strength, tough, and heat-resistant aluminum-magnesium alloy ingot of Example 7 after homogenization heat treatment is as follows: The ultralight, high-strength, tough, and heat-resistant aluminum-magnesium alloy ingot of Example 1 was subjected to homogenization heat treatment at 390°C for 18 hours to obtain an ultralight, high-strength, tough, and heat-resistant aluminum-magnesium alloy ingot after homogenization heat treatment.

[0111] The specific preparation method of the ultralight, high-strength, tough, and heat-resistant aluminum-magnesium alloy ingot of Example 8 after homogenization heat treatment is as follows: The ultralight, high-strength, tough, and heat-resistant aluminum-magnesium alloy ingot of Example 2 was subjected to homogenization heat treatment at 360°C for 15 hours to obtain an ultralight, high-strength, tough, and heat-resistant aluminum-magnesium alloy ingot after homogenization heat treatment.

[0112] The specific preparation method of the ultralight, high-strength, tough, and heat-resistant aluminum-magnesium alloy ingot of Example 9 after homogenization heat treatment is as follows: The ultralight, high-strength, tough, and heat-resistant aluminum-magnesium alloy ingot of Example 3 was subjected to homogenization heat treatment at 430°C for 20 hours to obtain an ultralight, high-strength, tough, and heat-resistant aluminum-magnesium alloy ingot after homogenization heat treatment.

[0113] The preparation methods of the ultralight, high-strength, tough, and heat-resistant aluminum-magnesium alloy ingots of Examples 10-12 after homogenization heat treatment are the same as those of the ultralight, high-strength, tough, and heat-resistant aluminum-magnesium alloy ingots of Example 8 after homogenization heat treatment.

[0114] The performance test results of the ultra-lightweight, high-strength, tough, and heat-resistant aluminum-magnesium alloy ingots after homogenization heat treatment are shown in Table 2.

[0115] The ultralight, high-strength, tough, and heat-resistant aluminum-magnesium alloy ingots of Comparative Examples 1-6 were applied to Comparative Examples 7-12 to prepare ultralight, high-strength, tough, and heat-resistant aluminum-magnesium alloy ingots that underwent homogenization heat treatment.

[0116] The performance test results of the homogenized heat-treated ultralight, high-strength, tough, and heat-resistant aluminum-magnesium alloy ingot are shown in Table 2. The fracture surface diagram of the homogenized heat-treated ultralight, high-strength, tough, and heat-resistant aluminum-magnesium alloy ingot of Example 7 is shown below. Figure 2 As shown.

[0117] Table 2 Test Results of Ultra-Light, High-Strength, Tough, and Heat-Resistant Aluminum-Magnesium Alloy Ingots (After Homogenization Heat Treatment) As can be seen from Table 2, the ultralight, high-strength, tough, and heat-resistant aluminum-magnesium alloy ingot of the present invention, after homogenization heat treatment, exhibits coarse grains continuously distributed along the grain boundaries. The phase is significantly reduced and dissolved back into the aluminum matrix, effectively eliminating the damage to plasticity caused by this brittleness. Simultaneously, within the aluminum matrix... The uniformity of TiC micron particle distribution is further improved, resulting in stronger overall mechanical properties of the ultralight, high-strength, tough, and heat-resistant aluminum-magnesium alloy ingot of the present invention.

[0118] Experimental Examples 1-6 The homogenized heat-treated ultralight, high-strength, tough, and heat-resistant aluminum-magnesium alloy ingots from Examples 7-12 were respectively applied to Experiments 1-6 to prepare ultralight, high-strength, tough, and heat-resistant aluminum-magnesium alloy plates 1# to 6#.

[0119] The specific preparation method of ultralight, high-strength, tough, and heat-resistant aluminum-magnesium alloy sheet No. 1 is as follows: The ultralight, high-strength, tough, and heat-resistant aluminum-magnesium alloy ingot of Example 7, after homogenization heat treatment, was placed in a tube furnace, held at 430°C for 30 minutes, and then rolled in 5 passes with equal reduction in each pass. The total reduction in hot rolling was 80%, and ultralight, high-strength, tough, and heat-resistant aluminum-magnesium alloy plate No. 1 was obtained after rolling.

[0120] The specific preparation method of ultralight, high-strength, tough, and heat-resistant aluminum-magnesium alloy sheet No. 2 is as follows: The ultra-light, high-strength, tough, and heat-resistant aluminum-magnesium alloy ingot of Example 8, after homogenization and heat treatment, was placed in a tube furnace, held at 400°C for 30 minutes, and then rolled in 5 passes with equal reduction in each pass. The total reduction in hot rolling was 70%, and ultra-light, high-strength, tough, and heat-resistant aluminum-magnesium alloy plate No. 2 was obtained after rolling.

[0121] The specific preparation method of ultralight, high-strength, tough, and heat-resistant aluminum-magnesium alloy sheet #3 is as follows: The ultralight, high-strength, tough, and heat-resistant aluminum-magnesium alloy ingot of Example 9, after homogenization heat treatment, was placed in a tube furnace, held at 415°C for 30 minutes, and then rolled in 6 passes with equal reduction in each pass. The total reduction in hot rolling was 90%, and the ultralight, high-strength, tough, and heat-resistant aluminum-magnesium alloy plate No. 3 was obtained after rolling.

[0122] The preparation methods for ultralight, high-strength, tough, and heat-resistant aluminum-magnesium alloy plates #4 to #6 are the same as those for ultralight, high-strength, tough, and heat-resistant aluminum-magnesium alloy plate #1.

[0123] The performance test results of ultralight, high-strength, tough, and heat-resistant aluminum-magnesium alloy plates 1# to 6# are shown in Table 3.

[0124] Comparative Test Examples 1-6 The homogenized heat-treated ultralight, high-strength, tough, and heat-resistant aluminum-magnesium alloy ingots of Comparative Examples 7-12 were respectively applied to Comparative Test Examples 1-6 to prepare plates D1# to D6#.

[0125] The preparation methods for plates D1# to D6# are the same as those for ultralight, high-strength, tough, and heat-resistant aluminum-magnesium alloy plate #1. The performance test results of the plates are shown in Table 3. The fracture surface diagram of ultralight, high-strength, tough, and heat-resistant aluminum-magnesium alloy plate #1 is shown below. Figure 3 As shown.

[0126] Table 3. Test results of sheet material performance As shown in Table 3, the rolled ultra-lightweight, high-strength, toughness, and heat-resistant aluminum-magnesium alloy sheets 1# to 6# of this invention exhibit a yield strength ≥ 517 MPa, tensile strength ≥ 670 MPa, and elongation ≥ 18.8%, significantly superior to sheets D1# to D6#. This indicates that the sheets of this invention possess excellent strength-plasticity synergistic matching effects. Simultaneously, the ultra-lightweight, high-strength, toughness, and heat-resistant aluminum-magnesium alloy sheets 1# to 6# have a hardness ≥ 180.1 HV and a specific strength ≥ 265.9. The results are significantly superior to those of plates D1# to D6#. Furthermore, this invention promotes grain refinement and texture optimization through rolling deformation, enabling the plate to maintain good plastic deformation capacity while achieving high strength. The above results demonstrate that the synergistic control strategy of "composition design—homogenization heat treatment—hot rolling process" established in this invention can effectively achieve a good match between plate strength and plasticity.

[0127] Test Example - Thermal Stability Test Ultra-light, high-strength, tough, and heat-resistant aluminum-magnesium alloy plates 1# to 6# and plates D1# to D6# were placed in a furnace at 200℃ for heat treatment. The furnace temperature was then raised to 300℃ and held for 1 hour. After the heat treatment was completed, the plates were allowed to cool naturally to room temperature in the air. The yield strength, tensile strength, elongation, and hardness of the ultra-light, high-strength, tough, and heat-resistant aluminum-magnesium alloy plates 1# to 6# and plates D1# to D6# were tested at room temperature (25℃). The results are shown in Table 4.

[0128] Table 4. Test results of thermal stability performance of the sheet material As shown in Table 4, after heat stability treatment at 300℃ / 1h, the yield strength retention rate, tensile strength retention rate, elongation retention rate, and hardness retention rate of the ultra-lightweight, high-strength, and high-toughness heat-resistant aluminum-magnesium alloy plates of this invention are all above 83%. Furthermore, the tensile strength of the ultra-lightweight, high-strength, and high-toughness heat-resistant aluminum-magnesium alloy plates #1 to #6 after heat treatment remains above 560 MPa, and the yield strength remains above 433 MPa, demonstrating excellent high-temperature structural stability and mechanical property retention. This is mainly attributed to two aspects: firstly, the synergistic formation of Sc and Zr... The nanophase possesses a core-shell structure, with the outer layer effectively suppressing diffusion and coarsening, allowing it to maintain its small size and continuously pin grain boundaries and hinder dislocation movement even at 300℃. On the other hand... TiC ceramic particles themselves possess extremely high thermal stability, exhibiting no decomposition or interfacial reaction at high temperatures. As a thermally stable reinforcing phase, they can continuously bear and transfer loads within the aluminum matrix. Simultaneously, homogenization treatment removes residual coarse particles from ultra-lightweight, high-strength, tough, and heat-resistant aluminum-magnesium alloy ingots that are prone to growth at high temperatures. The phase is fully re-dissolved, and the ... The phases are dispersed and fine after rolling, reducing the tendency for harmful phases to re-precipitate at high temperatures. The synergistic effect of the above-mentioned microstructures enables the composite material of the present invention to maintain high absolute strength and good plasticity reserve after heat exposure at 300℃ / 1h, indicating that the ultra-lightweight, high-strength, tough, and heat-resistant aluminum-magnesium alloy sheet of the present invention has outstanding thermal stability and resistance to high-temperature softening, and is suitable for lightweight structural component applications with high requirements for heat resistance.

[0129] Figure 1 The fracture surface diagram is shown for the ultralight, high-strength, tough, and heat-resistant aluminum-magnesium alloy ingot (without homogenization heat treatment) of Example 1. Figure 2 The fracture surface diagram is shown in Example 7, which is an ultra-lightweight, high-strength, tough, and heat-resistant aluminum-magnesium alloy ingot after homogenization heat treatment. Figure 3 The fracture surface diagram is shown for the ultralight, high-strength, tough, and heat-resistant aluminum-magnesium alloy plate #1 of Experimental Example 7. Figure 1-3It can be seen that the fracture surface of the ultra-light, high-strength, tough, heat-resistant aluminum-magnesium alloy ingot (without homogenization heat treatment) exhibits transgranular fracture characteristics, and the precipitated phases are distributed along the grain boundaries, indicating that its fracture is mainly brittle. Figure 2 The fracture surface of the homogenized alloy is a mixed fracture, and the precipitated phase is significantly reduced, indicating that the homogenization treatment effectively promotes the dissolution of harmful phases. Figure 3 The fracture surface of ultralight, high-strength, tough, and heat-resistant aluminum-magnesium alloy sheet #1 exhibits a mixture of dimples and quasi-dissociation characteristics, indicating that the material possesses a certain degree of plastic deformation capacity while achieving high strength. This demonstrates that the synergistic effect of homogenization heat treatment and hot rolling processes can effectively improve the fracture mode of the sheet, achieving a transformation from brittle to tough, thereby enhancing the overall mechanical properties of the material.

[0130] The above description is merely a specific embodiment of the present invention, but the scope of protection of the present invention is not limited thereto. Any variations or substitutions that can be easily conceived by those skilled in the art within the technical scope disclosed in the present invention should be included within the scope of protection of the present invention. Therefore, the scope of protection of the present invention should be determined by the scope of the claims.

Claims

1. A lightweight, high-strength, tough, and heat-resistant aluminum-magnesium alloy ingot, characterized in that, By weight percentage, the ultralight, high-strength, tough, and heat-resistant aluminum-magnesium alloy ingot comprises the following components: Mg: 7%-11%, Sc: 0.1%-0.4%, Zr: 0.1%-0.3%, ( Composite ball milling particles: 1.5%-2.5%, balance being Al and unavoidable impurities; Among them, the ( The composite ball milling particles contain Al powder, Powder and TiC powder.

2. The ultralight, high-strength, tough, heat-resistant aluminum-magnesium alloy ingot according to claim 1, characterized in that, The ( In the composite ball-milled particles, the Al powder, the... The mass ratio of the powder to the TiC powder is (1-3):1:1; and / or, The Al powder, the The average particle size of the powder and the TiC powder are each independently 1 μm-3 μm.

3. The ultralight, high-strength, tough, heat-resistant aluminum-magnesium alloy ingot according to claim 1 or 2, characterized in that, The ultralight, high-strength, tough, and heat-resistant aluminum-magnesium alloy ingot has a tensile strength ≥369MPa, a yield strength ≥280MPa, an elongation ≥4.6%, a Vickers hardness ≥95HV, and a density ≤2.54g / cm³.

4. A method for preparing an ultralight, high-strength, tough, heat-resistant aluminum-magnesium alloy ingot according to any one of claims 1-3, characterized in that, Includes the following steps: The raw materials are prepared according to the proportions of the ultra-lightweight, high-strength, tough, and heat-resistant aluminum-magnesium alloy ingots as described in any of claims 1-3. The raw materials include pure Al blocks, pure Mg blocks, Al-Sc master alloy, Al-Zr master alloy, and Al powder. Powder and TiC powder; The Al powder, the The powder and the TiC powder were ball-milled to obtain ( Composite ball milling particles; Under inert gas protection, the pure Al block is first melted at 740℃-760℃, then heated to 760℃-780℃, the Al-Sc master alloy and the Al-Zr master alloy are added for a second melt, then cooled to 700℃-720℃, the pure Mg block is added for a third melt, and then refined to obtain an alloy melt. The ( The composite ball milling particles are introduced into the alloy melt in an aluminum foil-wrapped manner for a first stirring, then cooled to 660℃-680℃ and held for 5-10 minutes, followed by a second stirring, casting, and cooling to obtain an ultra-light, high-strength, tough, and heat-resistant aluminum-magnesium alloy ingot.

5. The preparation method according to claim 4, characterized in that, The Al-Sc master alloy contains 2 wt.%-5 wt.% Sc; the Al-Zr master alloy contains 5 wt.%-10 wt.% Zr; and / or, The Al powder, the The powder and the TiC powder were ball-milled under inert gas protection conditions. The ball milling temperature was 10℃-30℃, the ball milling speed was 200r / min-300r / min, and the ball-to-material ratio was (9-20):

1.

6. The preparation method according to claim 4 or 5, characterized in that, During the first, second, and third smelting processes, a covering agent is added to the surface of the molten metal; the covering agent is a mixture of magnesium chloride, potassium chloride, and calcium fluoride; the mass ratio of magnesium chloride, potassium chloride, and calcium fluoride is (2-3):(2-3):1; the amount of covering agent added is 3%-4% of the total raw material mass; and / or, The refining temperature is 700℃-720℃; and / or, During the refining process, the refining agent used is a mixture of magnesium chloride, potassium chloride and calcium fluoride, wherein the mass ratio of magnesium chloride, potassium chloride and calcium fluoride is (1-2):(1-2):2; and the amount of the refining agent added is 3%-4% of the total raw material mass.

7. The preparation method according to claim 4 or 5, wherein the ( The composite ball milling particles are introduced into the alloy melt in an aluminum foil-wrapped manner. The temperature during the first stirring is 700℃-720℃, and the stirring speed during the first stirring is 150rpm-200rpm. The temperature is then lowered to 660℃-680℃ and held for 5min-10min. The stirring speed during the second stirring is 150rpm-200rpm.

8. The preparation method according to claim 4 or 5, characterized in that, After secondary stirring, casting, and cooling, and before obtaining the ultralight aluminum-magnesium alloy ingot, the process includes homogenization heat treatment and water quenching cooling steps; wherein the homogenization heat treatment temperature is 360℃-430℃, and the holding time is 15h-20h.

9. A lightweight, high-strength, tough, and heat-resistant aluminum-magnesium alloy sheet, characterized in that, The ultra-light, high-strength, tough, and heat-resistant aluminum-magnesium alloy ingot, prepared by any one of the ultra-light, high-strength, tough, and heat-resistant aluminum-magnesium alloy ingots according to any one of claims 1-3 or any one of claims 4-8, is then subjected to multiple hot rolling passes to obtain ultra-light, high-strength, tough, and heat-resistant aluminum-magnesium alloy plates.

10. The ultralight, high-strength, tough, and heat-resistant aluminum-magnesium alloy sheet according to claim 9, characterized in that, The multi-pass hot rolling temperature is 410℃~430℃, and the total reduction rate is 70%-90%; and / or, The ultralight, high-strength, tough, and heat-resistant aluminum-magnesium alloy sheet has a tensile strength ≥670MPa, a yield strength ≥517MPa, an elongation ≥18%, and a Vickers hardness ≥180HV; and / or, The ultralight, high-strength, tough, and heat-resistant aluminum-magnesium alloy sheet, after being heat-treated at 300℃ for 1 hour, has a tensile strength ≥560 MPa, a yield strength ≥433 MPa, an elongation ≥15.7%, and a Vickers hardness ≥150 HV.

Citation Information

Patent Citations

  • Lightweight high-strength corrosion-resistant aluminum alloy material and preparation method thereof

    CN116065066A

  • Lightweight high-strength high-toughness high-magnesium-content Al-Mg-Zn aluminum alloy and preparation method thereof

    CN121718770A